Effects of physical exercise to improve the body and behavioral composition of children with autism spectrum disorder (Research, Society and Development, 2023)
There are increasing cases of children with ASD in the world, we can say that today we already have millions of individuals with this disorder. Physical education offers children with ASD ways to express themselves and consequently benefits for psychomotor, social and cardiovascular health. This research aimed to address the topic of Autism Spectrum Disorder (ASD), highlighting its symptoms, the importance of early diagnosis and the growing incidence. It also emphasizes the need for public policies for prevention and treatment. The study proposes a narrative review on the effects of exercise on children with ASD, addressing the methodology used in the research, which included the search and analysis of 84 articles, resulting in 6 relevant to the topic. The results show that well-guided physical exercise proved to be a valuable tool for improving the quality of life of children with ASD, promoting improvements in body composition, behavior and social interaction.